Peran Guru Pendidikan Agama Islam dalam Kegiatan Sosial Keagamaan di Masyarakat: Diferensiasi dan Negosiasi Peran dalam Perspektif Role Theory - Wirdati Wirdati; Muhammad Ikhsan; Roza Susanti (An-Nuha, 2026)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers in the socio-religious activities of the community in West Payakumbuh District and to explain the social factors influencing variations in the enactment of these roles. The study employs a qualitative approach, with data gathered through observation, interviews with nine PAI teachers, and documentation. Data were analyzed interactively through data reduction, data presentation, and conclusion drawing. The results indicate that PAI teachers fulfill roles as correctors, inspirers, informants, organizers, motivators, initiators, guides, demonstrators, and mediators. However, the enactment of these nine roles is not uniform. Applying Role Theory, the study finds that the status of PAI teachers generates social expectations, while community trust provides the legitimacy enabling role enactment. Role differentiation is influenced by social proximity, community trust, the teacher's position within the socio-religious structure, community needs, personal motivation, as well as time constraints and other role demands. The role of PAI teachers in the community is not merely an extension of their teaching function from the school; rather, it is a social process negotiated among role expectations, social legitimacy, teacher capacity, and the community context. This study broadens the understanding of Islamic education as a process that unfolds not only within the classroom but also through the teacher's interaction with the community